Penerapan Foot Elevation 30 ̊ Terhadap Penurunan Derajat Oedema Ekstremitas Bawah Pada Pasien Congestif Heart Failure - Nur Farni Jafar; Arif Wahyu Setyo Budi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Heart and blood vessel disease has become an important public health problem and a major cause of death, so the role of nurses is very much needed in the management of heart failure patients. One effort that can be done independently by nurses in reducing oedema, especially oedema in the lower extremities or peripheral oedema is to do foot elevation therapy. The purpose of this case study was to provide nursing care by applying a foot elevation of 30 ̊ to reduce the degree of lower extremity oedema in patients with congestive heart failure. The method used in writing is a case report conducted for 3 days with a foot elevation intervention of 30 ̊. The results of this case study show that with the intervention of a foot elevation of 30 ̊ for 3 days, that is, there was a significant decrease in the degree of oedema in the lower extremities before the intervention was carried out with an oedema degree of 3 and after the intervention was worth 2. The effectiveness of applying standard nursing care in reducing oedema of the lower extremities given to patients shows a change in the reduction in the degree of oedema on the second day with a grade of oedema 2, namely with a depth of 3-5 mm with a return time of 5 seconds.